Common Polymorphisms in the MDM2 and TP53 Genes and the Relationship between TP53 Mutations and Patient Outcomes in Glioblastomas - Zawlik, Izabela (Brain Pathol, 2008)
MDM2 SNP309 is associated with younger age of tumor onset in patients with Li‐Fraumeni syndrome, and TP53 codon 72 polymorphism decreases its apoptotic potential. Glioblastomas frequently show genetic alterations in the TP53 pathway. In the present study, we assessed MDM2 SNP309 in 360 glioblastomas, and correlated these with patient age and survival, as well as other alterations in the TP53 pathway. Frequencies of the MDM2 SNP309 T/T, T/G and G/G genotypes in glioblastomas were 40%, 46% and 14%, respectively. Multivariate analysis showed that MDM2 SNP309 G/G allele was significantly associated with favorable outcome in female glioblastoma patients (hazard ratio 0.54; 95% CI = 0.32–0.92). There was a significant association between MDM2 SNP309 G alleles and TP53 codon 72 Pro/Pro in glioblastomas. Glioblastoma patients with TP53 codon 72 Pro/Pro genotype were significantly younger than Arg/Arg carriers (mean 50.2 vs. 56.1 years; P = 0.018). Multivariate analysis showed that those with TP53 codon 72 Arg/Pro allele had significantly shorter survival than those with Arg/Arg allele (hazard ratio 1.35; 95% CI = 1.07–1.71). Detailed analyses revealed that TP53 codon 72 Pro allele was significantly associated with shorter survival among patients with glioblastomas carrying a TP53 mutation, and among those treated with surgery plus radiotherapy.